Determination of Breast Cancer Fatalism in Women and the Investigation of the Relationship Between Women's Cervical Cancer and Pap Smear Test Health Beliefs with Religious Orientation and Fatalism - Bakan, Ayse Berivan (Journal of religion and health, 2021)
This study aims to determine breast cancer fatalism in women and investigate the relationship between women’s cervical cancer and pap smear test health beliefs with religious orientation and fatalism. The study, which was conducted as a descriptive and relational screening one, was conducted in the eastern part of Turkey between July and August 2019. The study was conducted with 357 women who were not diagnosed with breast or cervical cancer, and who were not pregnant. A positive, significant relationship was found between the Religious Orientation Scale total mean score and Health Motivation and Pap smear Benefit Perception sub-scale mean score. A positive, significant relationship was found between the Fatalism Tendency Scale total mean score and Sensitivity, Importance Perception, Pap smear Benefit Perception and Pap smear Barrier Perception sub-scale mean scores (p < .05). The participating women were found to have a low level of breast cancer fatalism. Religious Orientation and Fatalism Tendency were found to have affected the Cervical Cancer and Pap Smear Test Health Beliefs. Similar studies are recommended to be conducted in larger groups and different regions.